Evaporation variability of Nam Co Lake in the Tibetan Plateau and its role in recent rapid lake expansion - Ma, Ning; Szilagyi, Jozsef; Niu, Guo-Yue; Zhang, Yinsheng; Zhang, Teng; Wang, Binbin; Wu, Yanhong (Journal of hydrology (Amsterdam), 2016)
•Lake evaporation modeling without wind speed data.•CRLE model implicitly considers the wind effect via vapor transfer coefficient.•Evaporation decreasing was responsible for 4% of recent rapid Nam Co Lake expansion. Previous studies have shown that the majority of the lakes in the Tibetan Plateau (TP) started to expand rapidly since the late 1990s. However, the causes are still not well known. For Nam Co, being a closed lake with no outflow, evaporation (EL) over the lake surface is the only way water may leave the lake. Therefore, quantifying EL is key for investigating the mechanism of lake expansion in the TP. EL can be quantified by Penman- and/or bulk-transfer-type models, requiring only net radiation, temperature, humidity and wind speed for inputs. However, interpolation of wind speed data may be laden with great uncertainty due to extremely sparse ground meteorological observations, the highly heterogeneous landscape and lake-land breeze effects. Here, evaporation of Nam Co Lake was investigated within the 1979–2012 period at a monthly time-scale using the complementary relationship lake evaporation (CRLE) model which does not require wind speed data. Validations by in-situ observations of E601B pan evaporation rates at the shore of Nam Co Lake as well as measured EL over an adjacent small lake using eddy covariance technique suggest that CRLE is capable of simulating EL well since it implicitly considers wind effects on evaporation via its vapor transfer coefficient. The multi-year average of annual evaporation of Nam Co Lake is 635mm. From 1979 to 2012, annual evaporation of Nam Co Lake expressed a very slight decreasing trend. However, a more significant decrease in EL occurred during 1998–2008 at a rate of −12mmyr−1. Based on water-level readings, this significant decrease in lake evaporation was found to be responsible for approximately 4% of the reported rapid water level increase and areal expansion of Nam Co Lake during the same period.